Intralymphatic histiocytosis in a patient with lung adenocarcinoma treated with pembrolizumab: a case report. Issue 1 (27th February 2019) - Sugano, Teppei; Seike, Masahiro; Funasaka, Yoko; Yoshida, Mai; Takayama, Ryoko; Okamura, Ken; Nakanishi, Asuka; Tanaka, Toru; Takeuchi, Susumu; Noro, Rintaro; Minegishi, Yuji; Kubota, Kaoru; et al.
Abstract : Background: Pembrolizumab, an anti-programmed cell death-1 protein monoclonal antibody, is effective for patients with advanced non-small-cell lung cancer. However, immune checkpoint inhibitors such as pembrolizumab induce various immune-related adverse events, involving the lung, liver, gastrointestinal, endocrine system, and skin. Intralymphatic histiocytosis (ILH) is a rare, chronic cutaneous disorder with a reactive inflammatory component, which often occurs in patients with rheumatoid arthritis. Case presentation: We present a 67-year-old man with lung adenocarcinoma who developed ILH associated with pembrolizumab treatment. He was treated with palliative thoracic radiotherapy for superior vena cava syndrome. Subsequently, he received four cycles of pembrolizumab. Approximately 2.5 months after the initiation of pembrolizumab, he developed erythema on the trunk of his body. Based on findings of skin biopsies, he was diagnosed with pembrolizumab-induced ILH. Moreover, the upregulation of tumor necrosis factor-α was observed during pembrolizumab therapy. Conclusions: This is the first report of ILH induced by pembrolizumab in a patient with lung adenocarcinoma.